2009
DOI: 10.2319/100107-468.1
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Ozone on the Development of White Spot Lesions during Multibracket Appliance Therapy

Abstract: Objective: To test the null hypotheses: (1) there is no difference in the caries protective effect of ozone and Cervitec/Fluor Protector during multibracket (MB) appliance therapy, and (2) DIAGNOdent and quantitative light-induced fluorescence (QLF) are not superior to a visual evaluation of initial caries lesions. Materials and Methods: Twenty right-handed patients with a very poor oral hygiene who required full MB appliance therapy were analyzed during 26 months. In a split-mouth-design, the four quadrants o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 36 publications
0
31
0
1
Order By: Relevance
“…In dentistry, ozone was discussed in endodontic treatment since 1951 [25]; nevertheless, clinical studies are missing. Ozone was found to prevent white spot lesions in orthodontic patients [26] and to stop or reverse fissure and root caries lesions [27,28]. Knowledge about a possible usage of ozone in periodontitis and periimplantitis is extremely limited.…”
Section: Discussionmentioning
confidence: 99%
“…In dentistry, ozone was discussed in endodontic treatment since 1951 [25]; nevertheless, clinical studies are missing. Ozone was found to prevent white spot lesions in orthodontic patients [26] and to stop or reverse fissure and root caries lesions [27,28]. Knowledge about a possible usage of ozone in periodontitis and periimplantitis is extremely limited.…”
Section: Discussionmentioning
confidence: 99%
“…Huizinga et al (1991) calculated that CHX would be need to be released from the varnish for at least 6 months after a topical application (Huizinga et al, 1991). Some studies have shown the efficacy of CHX varnishes in decreasing the prevalence of caries during orthodontic treatment, yet other studies have not shown the efficacy of a varnish of 40% CHX (Kronenberg et al, 2009;Øgaard et al, 2001). Moreover, the main benefits of CPP-ACP are their ability to localize at the tooth's surface and penetrate into the supragingival plaque to provide bioavailable calcium and phosphate ions where they are most needed (Reynolds et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…When combining chlohexidine varnish with a fluoride varnish (Fluor Protector), the cariostatic effect was enhanced even further in comparison to ozone, which also have been shown to decrease S. mutans count. [86]…”
Section: Additional Methods To Prevent Wslmentioning
confidence: 99%